Effect of Zr additions on microstructure evolution and phase formation of Nb−Si based ultrahigh temperature alloys. (October 2018) - Sankar, M.; Phanikumar, G.; Singh, Vajinder; Satya Prasad, V.V.
Abstract: In the present work, the role of Zr addition on the microstructure and phase formation of hypoeutectic Nb−16 at. % Si alloy has been investigated. The results showed that both binary and alloy with 2 at. % Zr resulted in two phase microstructures composed of Nbss and Nb3 Si phases. In contrast, the alloys with 4 at. % Zr and 6 at. % Zr revealed two phase microstructures composed of Nbss and α−Nb5 Si3 phases. The orientation relationship (OR) obtained between eutectoid lamellar structure comprising of Nbss and α−Nb5 Si3 phases is (110) Nb//(110) Nb5 Si3 . The equilibrium microstructures consisting of Nb and α−Nb5 Si3 phases were obtained in as cast condition when the Zr concentration is above 2 at.%. The addition of Zr accelerated the dissociation kinetics of Nb3 Si phase in to Nbss and α−Nb5 Si3 phases during solidification. The formation of α−Nb5 Si3 phase in the as cast condition eliminates heat treatment required for decomposition of Nb3 Si phase in Nb-Si alloys. Highlights: Binary alloy and alloy with 2 at.%Zr alloys exhibit two phase microstructures composed of Nbss and Nb3 Si phases. Nbss and α−Nb5 Si3 phases are obtained in the as cast condition when Zr concentration exceed 2 at. %. The addition of Zr accelerates the dissociation kinetics of Nb3 Si phase. Zr is predominantly partitioned in Nb5 Si3 phase.